2021
DOI: 10.3390/s21155045
|View full text |Cite
|
Sign up to set email alerts
|

Fast Sensing of Hydrogen Cyanide (HCN) Vapors Using a Hand-Held Ion Mobility Spectrometer with Nonradioactive Ionization Source

Abstract: Sensitive real-time detection of vapors produced by toxic industrial chemicals (TICs) always represents a stringent priority. Hydrogen cyanide (HCN) is definitely a TIC, being widely used in various industries and as an insecticide; it is a reactive, very flammable, and highly toxic compound that affects the central nervous system, cardiovascular system, eyes, nose, throat, and also has systemic effects. Moreover, HCN is considered a blood chemical warfare agent. This study was focused toward quick detection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…We complete our study by examining precursors and/or simulants of CWAs as well as common interfering substances in order to estimate the extent of false positive alarms. As explained above, several factors affect the reduced ion mobility K 0 and usually lead to variations of approximately ±0.02 cm 2 / 25 manufacturer 33 Yamaguchi et al 34 Yang et al 35 Seto et al 29 Satoh et al 14 Bocos-Bintintan et al 15 device mini-IMS RAID- The ion polarity is given in brackets.K 0 values of this work are determined based on 1000 averaged ion mobility spectra. Vs or ±2% in the K 0 value of IMS-based instruments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We complete our study by examining precursors and/or simulants of CWAs as well as common interfering substances in order to estimate the extent of false positive alarms. As explained above, several factors affect the reduced ion mobility K 0 and usually lead to variations of approximately ±0.02 cm 2 / 25 manufacturer 33 Yamaguchi et al 34 Yang et al 35 Seto et al 29 Satoh et al 14 Bocos-Bintintan et al 15 device mini-IMS RAID- The ion polarity is given in brackets.K 0 values of this work are determined based on 1000 averaged ion mobility spectra. Vs or ±2% in the K 0 value of IMS-based instruments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The variation coefficient for the analyzed reference samples was not higher than permissible 20%. Obtained results showed that the method allows to differentiate nominal and elevated cyanide levels since the potentially toxic range is concentration 500 ng/mL–1 μg/mL [ 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples were analyzed in quadruplicate and an average concentration was 21.54 μg/mL (%RSD = 2.16), which is above the methods ULOQ (10 μg/mL). The determined cyanide in the blood proves a lethality of a suspected poisoning case as the concentrations above 2 μg/mL are generally considered as potentially life-threatening [ 26 ]. Besides, the white briquettes collected at the scene of the incident were evaluated qualitatively by preparing solutions at a concentration of 10 μg/mL and applying the described technique, they were confirmed as a cyanide salt.…”
Section: Discussionmentioning
confidence: 99%
“…time of flight ion mobility spectrometry), u negativnom ionskom modu. 69 Nakon ionizacije nastali ioni u pulsevima putuju kroz područje za odjeljivanje iona na koje djeluje homogeno električno polje te dolazi do skretanja i odvajanja iona zbog razlike u njihovoj pokretljivosti na koju utječu masa, veličina i oblik iona. Nakon odvajanja ioni dolaze na Fardayevu ploču (slika 10a).…”
Section: Spektrometrija Ionske Pokretljivostiunclassified